Post-weaning housing conditions influence freezing during contextual fear conditioning in adult rats - Schroyens, Natalie (2018)
The present study aimed to investigate the influence of housing conditions on contextual fear memory malleability. Male Wistar rats were housed in enriched, standard, or impoverished conditions after weaning and remained in these conditions throughout the entire experiment. After six weeks into those housing conditions, all animals underwent a 3-day protocol including contextual fear conditioning (day 1), memory reactivation followed by systemic administration of midazolam or vehicle (day 2), and a retention test (day 3). Percentage freezing was used as a behavioral measure of contextual fear. There was no evidence for an effect of housing conditions on the sensitivity of contextual fear memory to amnestic effects of post-reactivation midazolam administration, and no indication for amnestic effects of post-reactivation midazolam overall (including in the standard group). The inability to replicate previous demonstrations of post-reactivation amnesia using the same protocol underscores the subtle nature of post-reactivation pharmacological memory interference. Notably, impoverished housing resulted in a decrease in contextual freezing during contextual fear conditioning, reactivation and retention testing, compared to enriched and standard housing conditions. This observation warrants caution when interpreting the results from experiments regarding effects of housing on fear memory processes, particularly when freezing is used as a measure of fear.